CD137 ligand feedback upregulates PD‐L1 expression on lung cancer via T cell production of IFN‐γ. Issue 12 (17th October 2019) - Wang, Helin; Yan, Zhuohong; Hao, Jianqing; Yang, Bin; Wang, Jinghui; Yi, Ling; Wang, Xiaojue; Li, Shuping; Zhang, Hongtao; Zhang, Shucai
Abstract: Background: The expression of PD‐L1 and its regulation in tumors remains unclear. The importance of IFN‐γ in upregulating the PD‐L1 expression in various tumors, and the effects of other essential cytokines in the tumor microenvironment (TME), need to be further elucidated. Methods: Constitutive expression of PD‐L1 and CD137L in all 13 lung cancer cell lines were tested by flow cytometry. CD137L mRNA of lung cancer cell lines was detected by RT‐PCR. PD‐L1 expression rates following stimulation with these cytokines (IFN‐γ, TNFα and IL2) were measured. After coculture of cells expressing CD137L (lung cancer cells or 293FT cells transfected with CD137L plasmid) with T cells, the PDL1 expression of lung cancer cells and IFN‐γ in supernatant was detected. Results: Our data revealed that adenocarcinoma and squamous cell carcinoma cells had the highest positive expression rate. IFN‐γ was the core‐inducing factor for enhancing the PD‐L1 expression. CD137L was also widely expressed in the lung cancer cell lines at the mRNA level, whereas its expression was generally low at the protein level. However, the low expression of CD137L protein was still enough to induce T cells to produce IFN‐γ, which subsequently increased the PD‐L1 expression by lung cancer cells. The CD137 signal induces IFN‐γ secretion by T cells, which stimulates high‐level of PD‐L1 expression in cancer cells; this negative immune regulation may represent a mechanism of immune escape regulation. Conclusions: CD137L mRNA was widely expressed in lung cancer cell lines whereas levels of protein expression were generally low. The low level of CD137L protein was still enough to induce T cells to produce IFN‐γ that subsequently increased PD‐L1 expression. The CD137L‐induced negative immune regulation may represent a mechanism of immune escape.